Fifty years of communism in Russia - edited with an introd. by Milorad M. Drachkovitch. (Pennsylvania State University, 1968)
Ten papers originally given at an international conference held at Stanford University, Oct. 9-13, 1967. Sponsored by the Hoover Institution on War, Revolution, and Peace.